Obsession in death - Robb, J. D., 1950- (New York : G. P. Putnam's Sons, 2015)
NYPSD lieutenant Eve Dallas must contend with an admirer who proves his devotion by killing repeatedly.
Keywords: Dallas, Eve (Fictitious character) -- Fiction; Policewomen -- New York (State) -- New York -- Fiction; Murder -- Investigation -- Fiction; New York (N.Y.) -- Fiction